The college atlas, for schools and families; 36 maps, printed in colours with a complete index - wydawca (Frederick Warne and Co.Scribner, Welford, and Co., 1875)
[Zawartość k. 2].
Frederick Warne and Co. ; Scribner, Welford, and Co.
Keywords: Kartografia; atlasy szkolne; Świat; Rzeki; w kartografii; Góry; Izotermy; Opady; Norwegia; Palestyna; Prusy; Szwajcaria; Portugalia; Zabór rosyjski; Irlandia; Rosja; Zabór pruski; Afganistan; Wielka Brytania; Grecja; Walia (Wielka Brytania); Szwecja; Jerozolima (Izrael); Nowa Funlandia (Kanada); Francja; Niderlandy; Pakistan; Polska; Australia; Belgia; Ameryka Północna; Galicja; Turcja; Etiopia; Alpy; Ameryka Południowa; Kanada; Indie; Holandia; Szkocja (Wielka Brytania); Nowa Zelandia; Włochy; Europa; Niemcy; Półkula Zachodnia; Chiny; Afryka; Hiszpania; Stany Zjednoczone; Półkula Wschodnia; Republika Południowej Afryki; Austria; Egipt; Dania; Nubia